Determinants of Deflation in Hong Kong SAR - N'Diaye, Papa (IMF Working Papers; Working Paper ;, 2003)
This paper presents a comprehensive econometric analysis of the determinants of deflation in Hong Kong SAR. The analysis helps to determine the relative contributions of factors such as increased productivity, scarce money supply, and excess capacity in determining deflation. The main conclusion is that the effects of permanent shocks, such as productivity shocks and shocks related to changes in the money supply and price convergence with trading partners, have become more important in explaining deflation. In addition, the effects of temporary shifts in aggregate demand have been perpetuated by negative wealth and balance-sheet effects in the corporate and household sectors arising from asset-price declines over the past five years.